Management of Super-Obese Pregnancy – A Successful Outcome - Begum, Amena; Maruf, Abdullah Al; Shahida, SM (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Pregnancy associated with obesity is a challenge1.When surgical delivery is indicated that present a unique challenge2. A case of pregnancy with morbid obesity with a successful outcome is presented here. Bangladesh J Obstet Gynaecol, 2017; Vol. 32(1): 45-47